Gaussian solitary wave solutions for nonlinear perturbed Schrodinger equations with applications in nanofibers - Kaur, Lakhveer; Adel, Waleed; İnç, Mustafa; Rezazadeh, Hadi; Akinyemi, Lanre (World Scientific Publ Co Pte Ltd, 2024)
This paper presents an investigation into solutions of two types of nonlinear Schrodinger equations of logarithmic form. This model is of particular interest to researchers due to its vast application in the field of the implication of nanofibers. Through a comprehensive analysis, it was found that the solutions take the form of Gaussian-type solitary solutions. These solutions possess a variety of new structures due to the presence of many arbitrary constants and time-dependent functions in their general expressions. By fixing these constants and functions appropriately, Gaussian solitary waves for nonlinear perturbed Schrodinger equations can be represented, which could be beneficial in understanding the dynamics of these equations in nanooptical fibers. The results obtained from this study may provide a useful tool for further research into nonlinear Schrodinger equations and can be extended to fit more applications.
Keywords: Nonlinear perturbed Schrodinger equations; logarithmic nonlinearities; time-dependent coefficients; Gaussian solitary wave